Snake Envenomation Causing Distant Tracheal Myonecrosis - Amina Khimani; Afton Mcnierney; Sara Surani; Salim Surani (Case Reports in Pulmonology)
Snakebites are often believed to be poisonous. However, this is not always the case. In fact, each bite differs from snake to snake, depending on if the snake is poisonous and if there is envenomation. Venom in pit viper snakebites is often associated with local necrosis. The abundant literature selections and research articles justify local myonecrosis due to envenomation, but there is not much in the literature regarding myonecrosis at a site distant from the snakebite. We hereby present a case of a 42-year-old man who was transferred to our emergency department after a rattlesnake bit him twice. The patient, besides developing local myonecrosis at the site of the snakebite, developed necrosis of the scrotum as well as tracheal pressure myonecrosis at the site of the endotracheal tube balloon. In this review, we will attempt to discuss the myonecrosis pathophysiology and management related to the rattle snakebite.